2020
DOI: 10.1177/0748233719893178
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of bean cooking media containing EDTA in mice

Abstract: The possible renal and hepatic toxicities of ethylenediaminetetraacetic acid (EDTA) in bean cooking media were studied using 100 male albino mice. Two sublethal doses of EDTA were used to explore their toxic effects; 20 mg/kg and 200 mg/kg, which corresponded to 1/100th and 1/10th of LD50, respectively. Accordingly, the toxicity study was performed using 50 mice, divided into five groups ( n = 10/group) as follows: group 1 (Gp1) served as a negative control and was orally administered normal saline; group 2 (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Consistent with the hematological and biochemical ndings, the present study indicated that the effect of C.M./EDTA administration for 15 days did not alter both liver and kidney architecture, however, post 90 days of administration, C.M./EDTA (10 mg/Kg) induced histopathological alterations in the liver and kidney tissues. Similar ndings were found on the histopathological alterations of liver and kidneys upon administrating the experimental animals with C.M./EDTA for long time (El-Naggar et al 2019a). Wang et al (2004) reported that there was marked hepatocyte damage in rats administered with EDTA.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Consistent with the hematological and biochemical ndings, the present study indicated that the effect of C.M./EDTA administration for 15 days did not alter both liver and kidney architecture, however, post 90 days of administration, C.M./EDTA (10 mg/Kg) induced histopathological alterations in the liver and kidney tissues. Similar ndings were found on the histopathological alterations of liver and kidneys upon administrating the experimental animals with C.M./EDTA for long time (El-Naggar et al 2019a). Wang et al (2004) reported that there was marked hepatocyte damage in rats administered with EDTA.…”
Section: Discussionsupporting
confidence: 80%
“…This study was conducted to evaluate the effect of subacute and chronic administration of C.M./EDTA (10 mg/Kg) on the hepatorenal functions in the experimental mice. Previous study showed that administration of 20 mg/Kg or 200 mg/Kg led to toxic effects on the liver and kidney tissues in experimental animals that evidenced by the increase in ALT, AST, urea, and creatinine biomarkers and altered histological architectures of liver and kidney tissues (El-Naggar et al 2019a). In the present study, administration of C.M alone for 15 days (sub-acute), or 90 days (sub-chronic) did not signi cantly alter the body weight changes when compared to their control.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations